Praktik Sosiologi Keluarga Dalam Membangun Pendidikan Karakter Anak Di Era Digital - Lubis, Faizal Hamzah; Hardiyanto, Sigit (Universitas Muhammadiyah Sumatera Utara, 2024)
The practice of family sociology in the digital era has a great influence on children's character education. The digital era along with the development of information and communication technology has influenced family communication patterns. Communication between parents and children has undergone major changes. This article discusses changes in parent-child communication in the digital era and its impact on parent-child relationships. This article also discusses the positive and negative impacts of changes in communication between parents and children, as well as strategies that parents can use to optimize communication with children in the digital era. This research aims to analyze how the shift in family sociology can influence the process of children's character education. The research method used in this research is library research which aims to collect data and information by reviewing various sources including the Al-Quran, Hadith, scientific books, journals, documents and other writings as comparisons and supports used to obtain data. . The results of the analysis show that the digital era has brought changes in communication patterns within the family. Interactions between family members are often done via electronic devices, which can lead to a lack of face-to-face communication and a lack of time together. Apart from that, social media also has a big impact on children's experiences and exposure to content that may have negative risks.Keywords: Digital era; Family Sociology; Family Communication; Child Character.